"Four in one" model and the development of household biogas in northern China. (1st September 2004) - Wang, Gehua
By reviewing the development of household biogas in China, one of the key factors which impeded the use of biogas in northern China was noted - how a biogas digester lives through the winter. In order to solve this problem, a model named "Four in one" has been proposed by some researchers. In this paper, this model, including its structure, technical features, and benefit was introduced and analysed. And finally, with some statistics data, a conclusion was reached that the "Four in one" model has effectively promoted the development of biogas in northern China as well as providing valuable experiences for other developing countries.